Aplicación de GnRH en inducción de la ovulación para inseminación artificial de alpacas - Coronel Acuña, Mayra Cleofe (2021)
This research was carried out at the Salache Experimental Center, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, with the objective of evaluating the application of GnRH in ovulation induction for artificial insemination of alpacas whose study factors were follicular count, measurements of follicular diameter, ultrasound evaluation of the uterus, estrogen and progesterone levels, number of pregnant animals, GnRH dose, obtaining as a result a maximum of 8 follicles with an average of 7.5 mm in the application of 1.5 ml of GnRH. Regarding estrogen levels, it presents an average of 36.5 pg / ml at 0 ml doses and 23.4 pg / ml at 1.5 ml doses, in relation to progesterone, 0.15 ng / ml is obtained with 0 ml and 0.09 ng / ml with doses of 1.5 ml, of the same ones that a 100% pregnancy is obtained in T2. Concluding that there is no difference in the follicular diameter and if in the number of follicles in the levels of estrogens and progesterone there is a difference in their levels due to the same hormonal dynamics in their state of pregnancy. In general, in the research, a 75% pregnancy is reached, therefore, 1 ml or 1.5 ml of the ovulation inducer should be used since this way there are ideal and acceptable percentages in ovulation.